Perspektif Kajian Islam (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
Islamic studies is a learning material that is studied by students of Islamic colleges. It is also one component of general courses that must be taken by all students in all faculties and all majors. It covers a wide range of Islamic sciences, from the one dealing with the law, education, history, thoughts in Islam, even studies about the different kinds of approach in understanding the religion, the source of the teachings, the characteristic of Islamic teachings itself, to the methodology of understanding Islam in a comprehensive manner with diver theories along with model or type of the research. Such approaches include a "normative theological, anthropological, sociological, psychological, historical, cultural, and philosophical approaches"